Establishment and application of a quadruple real-time RT-PCR for detecting avian metapneumovirus. - Suchun Wang; Nan Jiang; Lijian Jiang; Qingye Zhuang; Qiong Chen; Guangyu Hou; Zhiyu Xiao; Ran Zhao; Yang Li; Chenglong Zhao; Fuyou Zhang; Jianmin Yu; et al. (PLoS ONE, 2022)
In order to develop an appropriate method for high-throughput detection of avian metapneumovirus, a quadruple real-time reverse-transcription polymerase chain reaction assay was established with four pairs of specific primers and four specific probes based on the G or M gene of aMPV-A, aMPV-B, aMPV-C and aMPV-D. Its specificity and sensitivity were evaluated, and clinical samples were tested by the method. The results showed that all the four subgroups of avian metapneumovirus can be detected in the quadruple real-time RT-PCR assay simultaneously, with a detection limit of 100-1000 cRNA copies/reaction. The other common poultry viruses were negative. In the avian clinical sample detection, 39 out of 1920 clinical samples collected from 8 provinces were positive. Compared with published RT-PCR assays, the κ value of the quadruple real-time RT-PCR assay in 1920 avian clinical samples was 1.000 (P < 0.001). The established method could be used for the rapid detection of the four subgroups of avian metapneumovirus with high specificity and high sensitivity.